Ethnic discrimination in Germany's labour market: a field experiment - Leo Kaas; Christian Manger (Institute for the Study of Labor (IZA), 2010)
This paper studies ethnic discrimination in Germany's labour market with a correspondence test. To each of 528 advertisements for student internships we send two similar applications, one with a Turkish-sounding and one with a German-sounding name. A German name raises the average probability of a callback by about 14 percent. Differential treatment is particularly strong and significant at smaller firms at which the applicant with the German name receives 24 percent more callbacks. Discrimination disappears when we restrict our sample to applications including reference letters which contain favourable information about the candidate's personality. We interpret this finding as evidence for statistical discrimination.
Keywords: C93; J71; 330; Ethnic discrimination; hiring discrimination; correspondence test; Ethnische Diskriminierung; Arbeitsmarktdiskriminierung; Türken; Arbeitsuche; Deutschland